Relação entre o transtorno de déficit de atenção e hiperatividade (TDAH) e a aprendizagem na produção do conhecimento em programas de pós-graduação em educação no Brasil - Santos, Crislene Gois (2019)
The attention deficit hyperactivity disorder (ADHD) is a clinical phenomenon of médico-psiquiátrico order, catalogued and classified by two international documents: DSM-V and ICD-10-the first adopts the terms of acronym ADHD and the second, use of the term "Hyperkinetic Disorder" (TH)-which serve to diagnose many people, especially in school age. With that, increasingly, is assigned to the educators teach children function and to attempted to the possible difficulties they may have in learning. Thus, the literature points out that it is for the teacher to be a helper function for diagnosis of possible disorders that interfere with the learning process, one of them being ADHD. This research aimed to centrally aimed at understanding, based on an analysis of seventeen (17) research, including theses and Brazilian dissertations in the area of education, what is the relationship between ADHD and learning. For this we opted for a quali-quantitative nature based on a literature review study, categorization and analysis of data from the suggested steps for Salvador (1981). To conceptualize and discuss the ADHD and learning, theoretical discussion was based on: Bachelard (1996); Muszkat (2012); Conceição (2015); Silva (2009); Rohde e Mattos (2008); Moysés and Collares (2010); Caliman and Domitrovic (2013); Souza (2017) Wajnsztejn and Malloy-Diniz (2010) among others. And to dialogue with the data found: Canguilhem (2009); Wallon (2007); Diaz (2011); Lefrançois (2008); Topczewski (1999); Boiaski (2007) and Rondini et al. (2015); the DSM-V (2014) and the ICD-10 (2009). In view of some categories, such as: attention, concentration, , imitation, interaction, memory, motivation, training and repetition, the present study could observe through the data, the discourses that scholars in education have been using to explain the pathological with a view to normality, as well as its scientific foundations, suggestive and interventive to restore order and learning within the school. Therefore, the data and discussions presented in this study, serve to observe not only the discourse of researchers in education, but also propose a reflection on the possibilities of thinking the other beyond their limitations and medical frameworks, pedagogical and social.